2006
DOI: 10.1002/ejoc.200600600
|View full text |Cite
|
Sign up to set email alerts
|

Recoverable Homogeneous Palladium(0) Catalyst for Cross‐Coupling Reactions of Arenediazonium Salts with Potassium Organotrifluoroborates: Detection of Catalytic Intermediates by Electrospray Ionization Mass Spectrometry

Abstract: Fifteen-membered triolefinic macrocyclic palladium(0) complex 1, (E,E,E)-1-ferrocenylsulfonyl-6,11-bis[(4-methylphenyl)sulfonyl]-1,6,11-triazacyclopentadeca-3,8,13-trienepalladium(0), is an active and recoverable catalyst for Suzuki-Miyaura cross-couplings between arenediazonium salts and potassium organotrifluoroborates. The reactions were performed under aerobic conditions at room temperature and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Arylation of olefins 2a-2e only gave products with the (E)-configuration, as was confirmed by the large coupling constant values (16)(17)(18) observed between the olefin protons for all compounds 3a-3e. Residual proton signals from a tentative (Z)-configurated isomer were never observed.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Arylation of olefins 2a-2e only gave products with the (E)-configuration, as was confirmed by the large coupling constant values (16)(17)(18) observed between the olefin protons for all compounds 3a-3e. Residual proton signals from a tentative (Z)-configurated isomer were never observed.…”
Section: Resultssupporting
confidence: 75%
“…[15] When we tested the optimized conditions for arenediazonium salts that we had previously established, [16] it was found that 2-methoxycarbonylthiophene-3-diazonium tetrafluoroborate 1 reacted efficiently (Table 3). When the thiophenediazonium salt and potassium phenyltrifluoroborate 5a were mixed with PdA C H T U N G T R E N N U N G (OAc) 2 as a palladium source in dioxane, a 77% yield of the arylated product 6a was obtained after 4 h of reaction at room temperature Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…The coupling of these two partners is a modification of the more popular Suzuki-Miyaura cross-coupling reactions in an attempt to improve and broaden the scope of this process [15]. One of the advantages of analyzing reaction intermediates using diazonium salts is that in the oxidative addition step a molecular nitrogen extrusion takes place to give arylpalladium species, whose cationic nature facilitates the monitoring of the reaction by means of ESI-MS. One of these studies, by Roglans et al, [16] uses Pd 2 (dba) 3 as a catalytic system (dba ¼ dibenzylideneacetone) and the other, by Mastrorilli et al [17], uses bis(m-acetato)bis(4,4 0 -difluoroazobenzene-C 2 ,N) dipalladium(II) as a precatalyst.…”
Section: +mentioning
confidence: 99%
“…Electrospray ionization mass spectrometry (ESI-MS) is a powerful tool in the identification of organometallic reaction intermediates and has been applied to the detection of intermediates in palladium-catalyzed cross coupling reactions. [15][16][17][18][19][20][21][22] However, these studies are essentially focused on the identification of palladium intermediates. Thus, we applied the ESI-MS in the negative mode to detect the boron species in the coupling reaction with (E)-bromostilbene.…”
Section: Resultsmentioning
confidence: 99%